Students at Shakespeare Press Museum (1969)
Two students operating an 1850s Washington Hand Press in the Shakespeare Press Museum to print a poster. On the right is Marcus Drake, student curator of the museum, and on the left is Jared Robinson. The Shakespeare Press Museum was opened at Cal Poly in 1969 and still operates in the Graphic Communication Building, Building 26. This photo was printed in the February 19, 1969 Mustang Daily.